2001
DOI: 10.1046/j.1440-1614.2001.00877.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk Factors for People with Mental Illness

Abstract: Psychiatric outpatients have a high prevalence of cardiovascular risk factors which may account for the higher rate of cardiovascular mortality among the mentally ill. Further research is needed to trial and evaluate interventions to effectively modify risk factors in this vulnerable population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
146
3
6

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(163 citation statements)
references
References 24 publications
8
146
3
6
Order By: Relevance
“…19 studies utilised SRQs Archie et al, 2007Arbour, Faulkner, & Cohn, 2010;Brown, Birtwistle, Roe, & Thompson, 1999, Brown, Goetz, Van Sciver, Sullivan, & Hamera, 2006Dubbert et al, 2006;Ellingrod et al, 2011;Elmslie, Mann, Silverstone, Williams, & Romans, 2001;Faulkner et al, 2006;Lassenigus, kerlind, Wiklund-Gustin, Arman, & Söderlund, 2013;Lindamer et al, 2008;McLeod, Jaques, & Deane, 2009;Osborn, Nazareth, & King, 2007;Ratliff et al, 2012;Ussher, 2003;Ussher, Doshi, Sampuran, & West, 2011;Van Citters et al, 2010;Vancampfort, Probst, Knapen, Carraro, & De Hert, 2012. Excluded studies (with reason) 55 did not use an outcome measure that provided an assessment of the three fundamental domains of physical activity Acil, Dogan, & Dogan, 2008;Adams, 1995;Aquila, 2000;Archie, Wilson, Osborne, Hobbs, & McNiven, 2003;Ball, Coons, & Buchanan, 2001;Barton, Griffin, & Pretty, 2012;Beebe et al, 2005;Bobes et al, 2010a,b, Bobes, Arango, Garcia-Garcia, & Rejas, 2010bBrill et al, 2007;Brunero & Lamont, 2010;Buhagiar, Parsonage, & Osborn, 2011;Centorrino et al, 2006;Charmove, 1986;Chuang, Mansell, & Pattern, 2008;Crone et al, 2004;Daumit et al, 2005;Davidson et al, 1999Davidson et al, , 2001…”
Section: The Identification Of the Different Outcome Measures Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…19 studies utilised SRQs Archie et al, 2007Arbour, Faulkner, & Cohn, 2010;Brown, Birtwistle, Roe, & Thompson, 1999, Brown, Goetz, Van Sciver, Sullivan, & Hamera, 2006Dubbert et al, 2006;Ellingrod et al, 2011;Elmslie, Mann, Silverstone, Williams, & Romans, 2001;Faulkner et al, 2006;Lassenigus, kerlind, Wiklund-Gustin, Arman, & Söderlund, 2013;Lindamer et al, 2008;McLeod, Jaques, & Deane, 2009;Osborn, Nazareth, & King, 2007;Ratliff et al, 2012;Ussher, 2003;Ussher, Doshi, Sampuran, & West, 2011;Van Citters et al, 2010;Vancampfort, Probst, Knapen, Carraro, & De Hert, 2012. Excluded studies (with reason) 55 did not use an outcome measure that provided an assessment of the three fundamental domains of physical activity Acil, Dogan, & Dogan, 2008;Adams, 1995;Aquila, 2000;Archie, Wilson, Osborne, Hobbs, & McNiven, 2003;Ball, Coons, & Buchanan, 2001;Barton, Griffin, & Pretty, 2012;Beebe et al, 2005;Bobes et al, 2010a,b, Bobes, Arango, Garcia-Garcia, & Rejas, 2010bBrill et al, 2007;Brunero & Lamont, 2010;Buhagiar, Parsonage, & Osborn, 2011;Centorrino et al, 2006;Charmove, 1986;Chuang, Mansell, & Pattern, 2008;Crone et al, 2004;Daumit et al, 2005;Davidson et al, 1999Davidson et al, , 2001…”
Section: The Identification Of the Different Outcome Measures Usedmentioning
confidence: 99%
“…One major problem of studies measuring physical activity is the failure of researchers to consider or justify why they have chosen a particular OBM or SRQ. For example past research studies (Archie et al, 2007;Brill et al, 2007;Buhagiar et al, 2011;Chuang et al, 2008;Crone et al, 2004;Daumit et al, 2005;Davidson et al, 1999;Davidson et al, 2001;Ellingrod et al, 2011;Elmslie et al, 2001;Farnam et al, 1999;Lassenigus et al, 2013;McCreadie, 2003;Osborn et al, 2007;Ratliff et al, 2012;Samele et al, 2007;SØrensen, 2006;Van Citters et al, 2010;Vancampfort et al, 2011a,b,c;Vancampfort et al (2011d) have utilised a specific SRQ and justified its choice solely on the original study which validated the SRQ. This is often problematic if the tool has been validated in a certain population or if the original study was not validated correctly.…”
Section: The Problems Regarding the Justification Of Outcome Measure mentioning
confidence: 99%
“…It remains possible that obesity is associated with other mental health problems, such as psychotic disorders, not assessed in the present study. 25 In conclusion, although obesity had associations with mental…”
mentioning
confidence: 90%
“…[2][3][4][5][6][7][8][9] Higher rates of physical illnesses in people with mental illness are found in psychiatric hospitals in the private sector, 10 publicly provided units and community out-patients, 11,12 as well as in general population studies. [13][14][15] Furthermore, preventable inequalities in life expectancy are getting larger. 16 For example, based on mental health service data for Western Australia (WA) from 1985 to 2005, Lawrence et al 16 found that discrepancies in the life expectancy between people with and without mental illness had increased during that period, with over three-quarters of excess death in the former group (77.7%) being attributed to CVD, respiratory disorders and other physical illnesses.…”
Section: Introductionmentioning
confidence: 99%